Adiponectin, apelin, and the Role of Oxidation and Antioxidants in Pregnant Women in Samarra City - shamel, Aya harith; Abdulrahman, Mostafa ali; abdulla, Khalida Khaleel (Journal of Science in Medicine and Life, 2025)
The aim of the research was to find the relationship between some physiological and biochemical variables in pregnant women and their effect on certain vital functions in the body before and during pregnancy. Samples were collected from women visiting Samarra General Hospital and the outpatient medical clinics in Samarra city during the period from mid-September 2023 to early November 2023. A total of 90 blood samples were collected and divided into three groups: (30) control samples from married women who are not pregnant and do not use contraceptives, (30) samples from pregnant women in the period of 4 to 6 months of pregnancy, and (30) samples from pregnant women in the period of 7 to 9 months of pregnancy. The results showed a significant increase (P ≤ 0.05) in the concentration of apelin in pregnant women during the period of 7-9 months of pregnancy (33.615 ± 110.332) compared to the groups of pregnant women during the 4-6 months period (12.557 ± 85.967) and the healthy control group (5.565 ± 50.045), with a significant difference between the pregnant women in the 4-6 months period and the control group. A significant increase (P ≤ 0.05) was also observed in the concentration of adiponectin in pregnant women during the 7-9 months period (0.682 ± 4.904) compared to the groups of pregnant women during the 4-6 months period (1.345 ± 4.194) and the healthy control group (0.461 ± 3.005), with a significant difference between the pregnant women in the 4-6 months period and the control group. Additionally, a significant decrease (P ≤ 0.05) was found in the concentration of catalase in pregnant women during the 7-9 months period (1.813 ± 4.465) compared to the groups of pregnant women during the 4-6 months period (0.880 ± 5.824) and the healthy control group (1.545 ± 10.272), but there was a significant increase in the control group compared to pregnant women in the 4-6 months period. A significant increase (P ≤ 0.05) was also observed in the concentration of MDA in pregnant women during the 7-9 months period (6.820 ± 24.016) compared to the groups of pregnant women during the 4-6 months period (11.600 ± 19.623) and the healthy control group (1.518 ± 8.813), with a significant difference between the pregnant women in the 4-6 months period and the control group.